(untitled) (Scientia Agricola, 2005)
In vitro organogenesis of passion fruit was studied by the induction of adventitious buds from leaf discs in culture media supplemented with benzyladenine (BAP) or thidiazuron (TDZ). To minimize adverse effects of ethylene accumulation on shoot development, silver nitrate (AgNO3) was added to the induction media. Both BAP (0; 2.2; 4.4; 6.6 µmol L-1) and TDZ (0; 1.1; 2.2; 3.4 µmol L-1) were effective in promoting shoot development. Although no significant differences were detected using AgNO3 (23.5 µmol L-1), buds grown in AgNO3-supplemented media were more vigorous. The number of explants with buds obtained using TDZ and AgNO3-supplemented media (5.6) were higher than those obtained using BAP and AgNO3 (3.0). MSM + giberrellic acid (GA3), MSM + coconut water, and ½ MSM culture media were tested for shoot bud elongation, incubated in flasks covered with either non-vented or vented lids. Best results were obtained by culturing buds in MSM + coconut water media in flasks covered with vented lids. Plantlets transferred to MSM + indol butyric acid (IBA) media rooted in a 30-day period. Passion fruit organogenesis was enhanced by using TDZ and AgNO3 for bud induction. Transferring the buds to MSM + coconut water media and incubating in flasks with vented lids favored shoot elongation and plantlet development.